Pengaruh Nilai Konsumsi dan Pembelian Impulsif terhadap Intensi Pembelian Virtual Item Pada Pemain Mobile Legends: Adventure - Budyastomo, Avin Wimar; Dianti, Hanifa Laila (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2022)
The main research of this study was to determine the influence of the value of consumption and impulsive purchases against the intention of purchase of virtual items on players of Mobile Legends: Adventure. The method used in this research is quantitative correlational. The population used in this research is the player of Mobile Legends: Adventure in the server SEA (South East Asia), which amounted to 34.852 people. The results of this study show that: (1) there is positive and not significant between the value of consumption to the intention of the purchase with a correlation coefficient of -0,002 and the coefficient of the significance of 0,980; (2) there is positive and not significant between impulsive purchases against the intention of the purchase with a correlation coefficient of -0.151 and the coefficient of the significance of 0,114; (3) there is a positive and significant influence between the value of consumption to the intention of the purchase simultaneous with a coefficient of multiple correlations of 0,238.